2022
DOI: 10.1186/s12879-021-06811-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between oral antimalarial medication administration and mortality among patients with Ebola virus disease: a multisite cohort study

Abstract: Background Empiric antimalarial treatment is a component of protocol-based management of Ebola virus disease (EVD), yet this approach has limited clinical evidence for patient-centered benefits. Methods This retrospective cohort study evaluated the association between antimalarial treatment and mortality among patients with confirmed EVD. The data was collected from five International Medical Corps operated Ebola Treatment Units (ETUs) in Sierra Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
(38 reference statements)
0
0
0
Order By: Relevance
“…15 Finally, there are a few studies with small numbers of patients that have found various interventions beneficial in reducing case fatality: multivitamins or vitamin A given within 48 hours of admission, 16,17 antibiotics such as thirdgeneration oral cephalosporins especially cefixime, 17 and use of empirical antimalarial treatment, especially artesunateamodiaquine rather than artemether-lumefantrine. 18,19 While existing published studies have examined risk factors for mortality, several reasons justify the need for additional research in this area. First, there have been conflicting findings between studies, especially with respect to clinical characteristics associated with mortality.…”
Section: Introductionmentioning
confidence: 99%
“…15 Finally, there are a few studies with small numbers of patients that have found various interventions beneficial in reducing case fatality: multivitamins or vitamin A given within 48 hours of admission, 16,17 antibiotics such as thirdgeneration oral cephalosporins especially cefixime, 17 and use of empirical antimalarial treatment, especially artesunateamodiaquine rather than artemether-lumefantrine. 18,19 While existing published studies have examined risk factors for mortality, several reasons justify the need for additional research in this area. First, there have been conflicting findings between studies, especially with respect to clinical characteristics associated with mortality.…”
Section: Introductionmentioning
confidence: 99%